ABURIZAL BAKRIE: DOMINASI IKLAN POLITIK & PERILAKU PEMILIH PEMULA DI KOTA YOGYAKARTA - , Ardian Bakhtiar Rivai ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study explains the influence of political advertisement on the political perception of first-time votersin Yogyakarta. Currently available theory takes two approaches: pluralistic approach that considers media having objectivity and no interest, and domination approach that thinks media is a political tool for certain group. Condition in Indonesia today in which many media entrepreneurs emerge as political candidates is obviously relevant to the media domination approach. The argumentation of this study is that mass media is an instrument for capitalist as also political candidate to influence first-time votersâ perception. Only the candidate or party with strong financial backing can compete to win the perception. It can be proved by measuring the influence of media (political advertisement) held by candidate to the perception of first-time voters, and new aspect of the argumentation is to focus the study on the voters. This study uses quantitative method using surveys of first-time voters in Yogyakarta. 350 third-year students of private and public senior high schools in Yogyakarta become samples with a margin of error of 5%. Cluster random sampling is used to select respondents representing 10 sub districts in Yogyakarta. The survey results show that political advertisements of Aburizal Bakrie are frequently showed on television. Indicators for measuring are television as the main information source, television watching routine, and personalization and emotional dimension about Aburizal Bakrie in the advertisement